ECONOMIC AND SOCIAL CONSEQUENCES OF OBESITY - Tursunov B. F.; Akhmedova D. B. (Web of Journals Publishing, 2025)
Obesity has become a serious global health issue, impacting not only physical health by increasing the risk of diabetes, cardiovascular diseases, and other chronic conditions but also the economy. The main causes of obesity include poor diet, reduced physical activity, and stress. This article examines the causes of obesity and its impact on social and economic sectors. It is expected that by 2025, the number of obese individuals will double, leading to additional burdens on healthcare systems.
Keywords: Obesity, healthcare, economic consequences, social issues, diabetes, cardiovascular diseases, physical activity, stress, global issue.